Monitoring Management of Arabic Language Teaching in Al-Azhar Cairo Islamic Elementary School Palembang - Rendi Sabana (Ittishal Educational Research Journal, 2020)
Arabic language is such an important language for non-Arab countries like Indonesia where its majority of population is moslem and they are the biggest moslem by number in the world. Al-Azhar Islamic Elementary School Palembang has implemented the valuable Al-Azhar Cairo curriculum and applied Arabic language as its learning language and used it for teaching and learning. Monitoring management in this school means an effort and a management for Arabic language teaching that students can achieve better results for them as well as evaluate their learning system effectively. The aim of this research is to analyze the monitoring management of Arabic language teaching in this Islamic elementary schools. This research is descriptive qualitative research and it’s done after collecting, analyzing and interpreting data and some research objects by descriptive method and collecting monitor-and –comparative-data. The data were taken from the headmaster of the school, Arabic language teachers as well as the students. This research concludes that the Arabic language teaching in this school is determined to good with good introduction and monitoring elements. But it still needs some improvement.